Coherent current states in a two-band superconductor - Yerin, Y.S.; Omelyanchouk, A.N. (Физика низких температур, 2007)
Homogeneous current states in thin films and Josephson current in superconducting microbridges are studied within the frame of a two-band Ginzburg–Landau theory. By solving the coupled system of equations for two order parameters the depairing current curves and Josephson current-phase relation are calculated for different values of phenomenological parameters and . Coefficients and describe the coupling of order parameters (proximity effect) and their gradients (drag effect), respectively. For definite values of parameters the dependence of current j on superfluid momentum q contains local minimum and corresponding bi-stable states. It is shown that the Josephson microbridge from two-band superconductor can demonstrate -junction behavior.